Bytelearn - cat image with glassesAI tutor

Welcome to Bytelearn!

Let’s check out your problem:

Rewrite the function by completing the square.

{:[f(x)=x^(2)-4x-26],[f(x)=(x+◻)^(2)+◻]:}

Rewrite the function by completing the square.\newlinef(x)=x24x26 f(x) = x^2 - 4x - 26 , f(x)=(x+)2+ f(x) = (x + \square)^2 + \square

Full solution

Q. Rewrite the function by completing the square.\newlinef(x)=x24x26 f(x) = x^2 - 4x - 26 , f(x)=(x+)2+ f(x) = (x + \square)^2 + \square
  1. Find constant term: First, we need to find the constant term that will complete the square. We take the coefficient of xx, which is 4-4, divide it by 22, and then square it.\newline(42)2=(2)2=4\left(\frac{-4}{2}\right)^2 = (-2)^2 = 4
  2. Add and subtract constant term: Next, we add and subtract this constant term (44) inside the function to complete the square, making sure the overall value of the function does not change.\newlinef(x)=x24x+4426f(x) = x^2 - 4x + 4 - 4 - 26
  3. Rewrite the function: Now we can rewrite the function by grouping the perfect square trinomial and combining the constants.\newlinef(x)=(x24x+4)426f(x) = (x^2 - 4x + 4) - 4 - 26
  4. Factor perfect square trinomial: The perfect square trinomial x24x+4x^2 - 4x + 4 can be factored into (x2)2(x - 2)^2.\newlinef(x) = (x2)2426(x - 2)^2 - 4 - 26
  5. Combine constants: Finally, we combine the constants 4-4 and 26-26 to get 30-30.\newlinef(x) = (x2)230(x - 2)^2 - 30

More problems from Solve a quadratic equation by completing the square